The optimization of various extraction method of dioscorine from dioscorea hispida dennst tuber - Fatin Nabilah Binti Ishak (2019)
Dioscorea hispida dennst (D.hispida) is a type of yam in the Dioscoreacea family that can be abundantly found in the tropical and subtropical country. It is commonly found in second growth forest and grows under shaded areas. The D.hispida tuber has become staple food in some part of place and brings benefit for many people as a therapeutic tools and insecticide. The tubers of D.hispida contain a neurotoxic of dioscorine which can cause food poisoning, vomiting, and paralysation of nervous system. Before consume it the detoxification must be performed to remove dioscorine. This study is to optimize the best extraction methods for isolating dioscorine from the D.hispida in powder form. The dioscorine was extracted by solid-liquid extraction methods and liquid-liquid extraction method. Different extraction methods were leaded to the different yield of extractive and functional group content of D.hispida. The results show that maceration assisted with ultrasonication probe type extraction method showed the highest amount yield of extractives is 6.74%, while Soxhlet extraction method showed 5.45% amount yield of extractives and ultrasonication bath was showed 5.36% and the least amount yield of extraction was chemical extraction method about 4.35%. The dioscorine functional group content from D.hispida was being identified by using Fourier Transform Infrared (FTIR) Spectroscopy and two methods extraction were showing complete compound of functional group of dioscorine. In this study dioscorine was utilize as an insecticide and evaluated using cognitive analysis.